PENGARUH PENERAPAN KURIKULUM KHAS TERHADAP PEMBENTUKAN KARAKTER SISWA DI SDIT PERMATA BUNDA - Evy Rukhayati; Ahmad Muflihin (Universitas Islam Sultan Agung, 2019)
The Integrated Islamic Schools Network (JSIT) applies a typical curriculum for Integrated Islamic Schools (SIT) to shape student character in accordance with the Quran and Sunnah. A typical curriculum is a curriculum that is applied and becomes a special feature of SIT, national curriculum development but is expanded and deepened by JSIT Indonesia and independent. This typical curriculum is applied with the aim of dealing with moral aspects that are often overlooked in the education process. This article aims to determine the effect of applying a typical curriculum to the formation of student character at SDIT Permata Bunda. This research is field research with quantitative methods using a questionnaire. The results showed that the calculated r-value of 0.119 was smaller than the r-value of table 0.220. So, it can be concluded that there is no influence between the application of a typical curriculum to the formation of student character at SDIT Permata Bunda. Therefore, there are several things that need to be evaluated so that the application of this typical curriculum can run more optimally.Keywords: Typical Curriculum, Formation of Student Character